Immediate effect of the rubber hammer on flexibility of superficial back line - Chakhuttray, Chaiwat; Siritaratiwat, Wantana; Mator, Lugkana; Boonprakob, Yodchai (Archives of Allied Health Sciences, 2019)
The purpose of this study was to test immediate effect of the rubber hammer on flexibility on the superficial back line in healthy participants. The study design was an assessor-blind randomized controlled trial. Thirty-six healthy participants were recruited, and were divided into 2 groups by block randomized allocation. Participants in the control group were asked to lie on their back comfortably, whereas participants in the experimental group were treated by the rubber hammer on the superficial back line in prone lying. Duration of testing was 18 minutes in both groups. Sit and reach test, straight leg raising (SLR) test, and Modified Schober ‘s test were performed to detect change of body flexibility. Body flexibility in the experimental group was increased significantly (p < 0.05) using by sit and reach test when compared within group. It was change from -3.98±2.18 to -1.45±3.79 (95%CI 1.04 to 4.02) centimeter whereas; body flexibility in the control group was not changed (p > 0.05). However, body flexibility in the experimental group was increased significantly when compared between groups (p < 0.05) In case of comparison within the group, angle of hip flexion in the experimental group was increased significantly (p < 0.05) using by SLR test. Hip flexion angle of the left side was change from 61.92±8.53 to 66.49±9.98 (95%CI 2.44 to 6.70) degree while hip flexion angle of the right side was change from 61.70±10.67 to 66.68±11.43 (95%CI 3.21 to 6.76) degree, while the hip flexion in the control group was did not change (p> 0.05). Change of hip flexion angle in the control group did not increase (p > 0.05). In case of comparison between groups, hip flexion angle in the experimental group was increased more than the control group significantly (p < 0.05). However, there was no change in inter-segmental movement of the thoracolumbar regions using by Modified Schober’s test for both within and between groups (p > 0.05). In conclusion, applying the rubber hammer on SBL showed immediate effect to increase body flexibility by sit and reach test and straight leg raising test.